Crack Initiation Assessment of Wearing Course Asphalt Mixtures Using Aggregate Gradation Characteristic - Haryanto, Iman; Takahashi, O (ITB Journal Publisher, LPPM ITB, 2007)
At normal service temperatures, wearing course asphalt mixtures may have ductile cracking. Aggregate gradation characteristic is important to avoid the premature cracking. The present study discusses a relationship between the characteristic of aggregate gradation and crack resistance of wearing course mixtures. Asphalt mixture specimens were prepared using different types of aggregate gradation. The Bailey method was employed in order to recognize the characteristic of aggregate gradations. Notched semi circular bending test was conducted to obtain the critical J integral (Jc). The coarse aggregate (CA) ratio and the fine graded fine aggregate coarse (FG FAc) ratio defined by the Bailey method were introduced to recognize the effect of aggregate gradation type on Jc. The result was decreasing the Jc value with increasing the CA ratio and FG FAc ratio. Satisfying the current Bailey criterion on the CA ratio for stone mastic asphalt mixtures and setting FG FAc of fine graded HMA mixtures near 0.4 seem useful in order to obtain HMA mixtures with a high Jc. The present study also discusses spherical aggregates assembly models as an aid to illustrate development of the aggregates interlocking, which influences to the cracking.